Between hope and reality: Challenges of islamic education teachers in implementing the independent curriculum at muhammadiyah 5 junior high school surakarta - Muhammad Alfan Wiandani; Isfihani; Iffah Mukhlisah (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to comprehensively describe the implementation of the "Kurikulum Merdeka" (Independent Curriculum) by Islamic Religious Education (PAI) teachers at Muhammadiyah 5 Junior High School Surakarta in the 2024/2025 academic year, as well as to identify the problems encountered and the efforts made to address them. A descriptive qualitative approach was employed, utilizing observation, in-depth interviews, and documentation as data collection techniques. The research subjects included the principal and two PAI teachers. The findings revealed that the Kurikulum Merdeka has been implemented across all classes, using CP/ATP and modules prepared by the central Muhammadiyah foundation. PAI teachers actively contextualize their instruction by integrating Islamic values and discussing contemporary social issues relevant to students’ lives. Nonetheless, they face several challenges, including difficulties in applying differentiated instruction, limited time for formative assessments, and a lack of technical training. To address these challenges, the teachers engage in reflective teaching practices, attend internal workshops and online training, share best practices with peers, and improve their assessment design skills. The study concludes that successful implementation of Kurikulum Merdeka requires strong institutional support and continuous professional development. The findings imply the need for collaborative strategies among the government, foundations, and schools to empower teachers in navigating the complexities of the new curriculum.